If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -2)(x + -2) = 64 Reorder the terms: (-2 + x)(x + -2) = 64 Reorder the terms: (-2 + x)(-2 + x) = 64 Multiply (-2 + x) * (-2 + x) (-2(-2 + x) + x(-2 + x)) = 64 ((-2 * -2 + x * -2) + x(-2 + x)) = 64 ((4 + -2x) + x(-2 + x)) = 64 (4 + -2x + (-2 * x + x * x)) = 64 (4 + -2x + (-2x + x2)) = 64 Combine like terms: -2x + -2x = -4x (4 + -4x + x2) = 64 Solving 4 + -4x + x2 = 64 Solving for variable 'x'. Reorder the terms: 4 + -64 + -4x + x2 = 64 + -64 Combine like terms: 4 + -64 = -60 -60 + -4x + x2 = 64 + -64 Combine like terms: 64 + -64 = 0 -60 + -4x + x2 = 0 Factor a trinomial. (-6 + -1x)(10 + -1x) = 0Subproblem 1
Set the factor '(-6 + -1x)' equal to zero and attempt to solve: Simplifying -6 + -1x = 0 Solving -6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -1x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = 0 + 6 -1x = 0 + 6 Combine like terms: 0 + 6 = 6 -1x = 6 Divide each side by '-1'. x = -6 Simplifying x = -6Subproblem 2
Set the factor '(10 + -1x)' equal to zero and attempt to solve: Simplifying 10 + -1x = 0 Solving 10 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -1x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -1x = 0 + -10 -1x = 0 + -10 Combine like terms: 0 + -10 = -10 -1x = -10 Divide each side by '-1'. x = 10 Simplifying x = 10Solution
x = {-6, 10}
| 12(z+1)-4(2-2)=4(z-4)+3(2-4) | | 2x^2-2+130=0 | | v^2-5v=-4 | | -14-5(x+2)=2x-6(x+3) | | 10(x+1)=0 | | 3x+7x+11=3x+25 | | 8v-24=432 | | 3x-15=6x-9y | | 13+17m-8= | | 1/5x=x-12 | | 5h+2(11-h)=15 | | 5(x-1)=65 | | 11w+12w-7+5=-3w+5-7 | | 11w+21(3w-1)=15w | | 2-1/7x=4 | | 3+12x-5=22 | | 25(4x+2)=150 | | 8x+3y-5x+7-10y+2= | | 4x-12x-12x+36=4x^2+36 | | (7j-h)(7j-h)(7j-h)= | | x^2+105=5 | | ln(2)=.69 | | 3n+5n=8 | | 1-x-6x=-6 | | X+6-3=-3 | | 13(9x-6)=6x-4 | | w+1.2=16.2 | | 12.12=3v | | (4x-5y+3z)+(-4x+5y+3z)= | | 2(3R-2)=4(R+4) | | -139-2x=57-9x | | 15+4x=7x+48 |